2015
DOI: 10.1038/nplants.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

Climate-induced reduction in US-wide soybean yields underpinned by region- and in-season-specific responses

Abstract: The United States is one of the largest soybean exporters in the world. Production is concentrated in the upper Midwest(1). Much of this region is not irrigated, rendering soybean production systems in the area highly sensitive to in-season variations in weather. Although the influence of in-season weather trends on the yields of crops such as soybean, wheat and maize has been explored in several countries(2-6), the potentially confounding influence of genetic improvements on yields has been overlooked. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 14 publications
10
58
0
Order By: Relevance
“…For each 0.8°C increase above 26.7°C, the current mean temperature of the southern United States, soybean yields are expected to decline by 2.4% (Hatfield et al, ). Similar reductions in soybean yield by high temperature have been reported for the United States (Lobell & Field, ; Mourtzinis et al, ) and across the globe (Mohanty et al, ). The average reduction in soybean yield was 3.1%/°C rise above the present temperatures (Lobell & Field, ; Schlenker & Roberts, ; Zhao et al, ).…”
Section: Introductionsupporting
confidence: 75%
“…For each 0.8°C increase above 26.7°C, the current mean temperature of the southern United States, soybean yields are expected to decline by 2.4% (Hatfield et al, ). Similar reductions in soybean yield by high temperature have been reported for the United States (Lobell & Field, ; Mourtzinis et al, ) and across the globe (Mohanty et al, ). The average reduction in soybean yield was 3.1%/°C rise above the present temperatures (Lobell & Field, ; Schlenker & Roberts, ; Zhao et al, ).…”
Section: Introductionsupporting
confidence: 75%
“…Nevertheless, this is an older study in which the hypothetical zones were based on photoperiod. Although photoperiod did not change, it has been shown that in-season temperatures increased in North Dakota since 1994 (Mourtzinis et al, 2015) which could have allowed for earlier planting of MG 0 varieties. Since photoperiod of a given location during specific months is constant through time, the difference among the zones reported in 1970 (Scott and Aldrich, 1970), 2003(Zhang et al, 2007, and our study suggest that the effect of temperature, driven by climate change, is also an important factor that affects the adaptation potential of different soybean MGs.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the management practices applied in variety trials (row spacing, seeding rate etc.) varied among states as well as their effect on soybean yields the past 20 yr (Mourtzinis et al, 2015). Additionally, the climatic conditions have been variable over the past 20 to 80 yr and it has been shown that the observed elevated temperatures have had variable results on soybean yield across the United States (Mourtzinis et al, 2015).…”
Section: S Oybean Is the Most Important Oilseed Crop In The Unitedmentioning
confidence: 99%
“…Weather, in particular temperature, and photoperiod, determine the length of the growing season from the first day of suitable planting conditions to the first suitable day for harvest (Archontoulis, Miguez, & Moore, 2014). Weather and photoperiod influence photosynthesis, heat stress and water stress thereby affecting the initiation of crop growth stages (Mourtzinis et al, 2015). Decreased photoperiod and radiation lead to decreased photosynthesis, which delays crop development while delayed planting shifts the grain filling period into a less favorable environment with shorter photoperiod and lower temperatures (Chen & Wiatrak, 2010).…”
Section: Introductionmentioning
confidence: 99%